2018
DOI: 10.1530/endoabs.56.gp127
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in a nationwide population of Danish women with polycystic ovary syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) is associated with obesity and low grade inflammation and the risk for cardiovascular disease (CVD) could be increased in PCOS. Methods: National register-based study including women with PCOS and no previous diagnosis of CVD, hypertension, or dyslipidemia. PCOS Denmark (N = 18,112) included women with PCOS in the Danish National Patient Register. PCOS Odense University Hospital (OUH, N = 1165) was an embedded cohort including premenopausal women with PCOS and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 11 publications
2
63
1
4
Order By: Relevance
“…Inclusion of women aged 30 years or more did not change significant results. Some limitations may apply to the present study design . Education level in immigrants could be underestimated, as their education must be individually reported to Statistics Denmark whereas education completed in Denmark is already in the registers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of women aged 30 years or more did not change significant results. Some limitations may apply to the present study design . Education level in immigrants could be underestimated, as their education must be individually reported to Statistics Denmark whereas education completed in Denmark is already in the registers.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and baseline data for this study cohort have been reported in detail earlier . Data regarding development of type 2 diabetes, cardiovascular disease and incident fractures in the study cohort have been published recently. We included two patient populations with PCOS and one control population (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…107 Additionally, in a recently published national register-based study with over 70 000 participants, authors from Denmark noted significantly higher incidence rate of CVD in PCOS women than in controls respectively 22.6 and 13.2 per 1000 person-years. 108 Moreover, incidence rate of CVD excluding AH and dyslipidaemia was estimated at 6.4 per 1000 person-years in PCOS group and 4.5 in controls, that was still statistically significant, and the median age at the diagnosis of CVD was significantly lower in PCOS than in controls (35 vs 36 years). It was also demonstrated that obesity, T2DM, infertility, and previous use of oral contraceptives were associated with increased risk of CVD in PCOS women.…”
mentioning
confidence: 89%
“…PCOS may also be associated with increased incidence of cardiovascular disease and this risk should be considered even in young women with PCOS [11]. Surrogate markers of cardiovascular disease are already altered in adolescent PCOS ladies and metformin treatment positively modified these markers leading to the proposal of a preventive treatment [12].…”
Section: Introductionmentioning
confidence: 99%